Vaccination Perceptions of College Students: With and without Vaccination Waiver - Jadhav, Emmanuel D.; Winkler, Danielle L.; Anderson, Billie S. (Frontiers in Public Health, 2018)
Introduction: The resurgence of vaccine preventable diseases occurs more often among intentionally unvaccinated individuals, placing at direct risk young adults not caught up on vaccinations. The objectives of this study were to characterize the sociodemographic characteristics of young adults with and without vaccination waivers and identify their perceived benefits, barriers, and influencers of vaccination. Methods: Young adults (n=964) from a Midwestern rural university responded to a survey (fall 2015 - spring 2016) designed to identify their perception towards vaccination. Instrument consistency was measured using the Cronbach α-scores. The Chi-square test was used to test any sociodemographic differences and Mann-Whitney U-tests results for differences between exempt and non-exempt students. Analysis occurred in spring 2017. Results: A little over one-third of young adults with a vaccination waiver were not up to date on their vaccinations, and think that vaccinations can cause autism. The biggest identifiable benefit was effective control against disease. The out of pocket cost associated with vaccination was the most reported barrier and vaccines that are safe and easy to use was the most important influencer of vaccination. Conclusions: Young adults who have had a vaccination waiver appear to not be up to date on their vaccinations. Vaccine administration programs, such as university campus clinics, would benefit from addressing perceptions unique to young adults with and without a vaccine waiver. This would subsequently better provide young adults a second shot for getting appropriately caught up on vaccinations.